Penerapan Metode Extended Promethee II (EXPROM II) Dalam Penyeleksian Siswa Pada Jurusan Ground Support Equipment (GSE) Operator Nadarya Aviation Center Medan - Eka Murlisah; Mesran Mesran (Journal of Computer System and Informatics (JoSYC), 2021)
The Nadarya Aviation Center (NAC) Aviation Training Institute is a private training institution that aims to prepare skilled, work-ready, mentally strong, responsible human resources, have faith and piety, have quality and are able to compete independently and professionally. Ground Support Equipment (GSE) Operator is an aircraft ground service equipment personnel who has a license and rating to carry out the operation of aircraft ground service equipment while the aircraft is on the ground (apron / aircraft parking at the airport). It is hoped that an effective selection process will be able to screen training students in the GSE Operators department who really fit the target desired by the Director of the flight training institute. One of the right solutions for these problems is to use a Decision Support System (DSS). Decision Support Systems (DSS) can assist aviation training institutions in making student selection decisions for the right operator ground support equipment (GSE) majors and will increase the efficiency of these decisions. Extended Promethee II (EXPROM II) is a method of decision making on preference functions with problems through the outranking approach or is a multicriteria analysis, comparing one alternative with another and calculating the difference between the alternative pairs to produce an output that is an alternative ranking based on value. highest